Standards of the nursing knowledge and its interface to the attendance to the domiciliary - a literature review - Maria R Lacerda; Ivete PS Zagonel; Soriane K Martins (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
The attendance to the domiciliary health resurges as an alternative modality to the model of attention to the health of the country and the professional nurse who acts in this area as commitment and responsibility to improve its knowledge. Thus, this article, is a theoretical reflection on the interface of the standards of the knowledge of nursing identified by Barbara Carper (1978), Munhall (1993), White (1995) and brazilians studious where they point the possibility, importance and relevancy with respect to the area of nursing and in special in domiciliary attendance to the health while caring practice that confers an uneven and particular situation to the inserted client in its domicile. This interface is based on the reciprocity with the well-taken care of being, propitiating learning and growth conditions, in order to contribute for the consolidation of new experiences, enriching the capacity to take care of the nurse, patient and family member.